Analisis Perkembangan Sosio-Emosional Anak Kelas V Selama Pelaksanaan Belajar dari Rumah - Rahmani Zahroh; Badruli Martati; Fajar Setiawan (Edumaspul: Jurnal Pendidikan, 2022)
This article was prepared with the aim of analyzing the socio-emotional development of fifth graders and to find out problems related to socio-emotional development that arise during learning from home. This study uses a qualitative descriptive method with data sources consisting of classroom teacher interviews, observations, questionnaires and documentation. The results of this study indicate that during the implementation of learning from home, the socio-emotional development of fifth graders continues but there are several problems that arise related to regulating emotions, using emotions effectively and establishing relationships. For example, students tend to take aggressive actions as a form of conveying emotions, lack of sense of responsibility for tasks, and low ability to establish social relationships. These problems can occur due to several causes such as limited interaction and communication between teachers and students, the inability of parents to replace the teacher's role to guide and control students and changes in the environment and student learning styles. Therefore, it is hoped that further researchers will be able to identify further and find ways to solve the problems that arise.